2022
DOI: 10.1515/med-2022-0426
|View full text |Cite
|
Sign up to set email alerts
|

Staple line reinforcement with nebulized cyanoacrylate glue in laparoscopic sleeve gastrectomy: A propensity score-matched study

Abstract: Background A dreaded complication of laparoscopic sleeve gastrectomy (LSG) is suture leak. The study aimed to assess the efficacy of the nebulized comonomer Glubran 2® (N-butyl-cyanoacrylate + metacrylosysolfolane) applied to the LSG staple line. Methods A propensity-matched comparison analysis was conducted in 125 patients undergoing LSG between 2017 and 2019. Groups included those treated with Glubran® (group 1, n = 70) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, pro-inflammatory effects have been documented [10]. Some studies reported favorable results with modified cyanoacrylate, Glubran ® 2 (GEM Srl, Viareggio, Lucca, Italy), associated with chemical omentopexy [61][62][63]. Intraoperative reinforcement with tissue sealants at the time of the SG has been explored, and some authors conclude a decreased risk of complications including leaks [64,65].…”
Section: Endoscopic Tissue Sealant Applicationmentioning
confidence: 99%
“…However, pro-inflammatory effects have been documented [10]. Some studies reported favorable results with modified cyanoacrylate, Glubran ® 2 (GEM Srl, Viareggio, Lucca, Italy), associated with chemical omentopexy [61][62][63]. Intraoperative reinforcement with tissue sealants at the time of the SG has been explored, and some authors conclude a decreased risk of complications including leaks [64,65].…”
Section: Endoscopic Tissue Sealant Applicationmentioning
confidence: 99%
“…Among the possible options to reinforce and protect anastomosis, cyanoacrylate glue application has signi cantly reduced AL in colon anastomosis in a porcine model [17][18][19][20] and prevents suture leakage after sleeve gastrectomy [21]. Furthermore, cyanoacrylate is widely used in endoscopy for the emergency management of patients with upper gastrointestinal bleeding because of its adhesive and haemostatic seal when nebulised and sprayed on injured tissues [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the sealing effect creates an antiseptic barrier against bacteria [23]. The application of cyanoacrylate glue in vascular surgery [24], urology [25], and bariatric surgery [21] has been previously described.…”
Section: Introductionmentioning
confidence: 99%